Analisis Kinerja Keuangan Perusahaan Merger dan Akuisisi ( Studi Kasus Perusahan Manufaktur di Bursa Efek Indonesia Tahun 2014 – 2016) - I Made Murjana; Ulfiyani Asdiansyuri (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
Facing increasingly fierce competition, encouraging companies to implement various short-term and long-term business strategies. One way to do this is merger and acquisition. The merger is expected to increase market share, business diversification, or improve vertical integration of existing operational activities. The purpose of this study is to determine the financial performance of companies that are mergers and acquisitions. Comparative descriptive research with techniques for collecting data through documentation. The total population of merger and acquisition companies in 2014-2016 was 22, taken as a sample of 8 companies. Sampling techniques Non probability sampling with a purposive sampling approach. Analysis techniques through the financial ratio (NPM), (TATO), and (ROA) approach. The results of the study show that companies that have mergers and acquisitions have good performance and some that perform poorly.